Taking HIV Out of the Equation? A phenomenological exploration of a small group of gay men’s meaning making around sexuality whilst on PrEP (Existential Analysis: Journal of the Society for Existential Analysis, 2021)
This article explores, through a phenomenological IPA study, in which 8 semi-structured interviews were conducted, what meaning gay men on pre-exposure prophylaxis (PrEP) make of their sexuality, and examines how sexuality is experienced through lenses of being and doing, how it is spoken about, and how the threat of HIV is still prevalent.
Keywords: Phenomenological analysis; IPA; sexuality; being sexual; PrEP; HIV; meaning; gay